Why Chinese Consumers Prefer the Wet Market Rather Than the Supermarket for Daily Food Consumption -An Investigation in Chinese Food Shoppers - JI, Yan (2009)
This paper aims to explore Chinese consumers shopping intentions and decisions to purchase food and hence to explain why Chinese consumers prefer to shop in traditional markets rather than supermarkets for daily food consumption. The survey is conducted by asking the participants eight well-structured questions and all the participants are the consumers who have relevant shopping experiences with both the supermarket and the wet market. It is found that when compared with the wet market, the advantages of the supermarket are apparent. These advantages include higher quality goods, wider range of choices, higher quality shopping environment and better store atmospherics. And in addition, the economies of scale enable the supermarket to afford price competition and various promotion activities. While the finding explores that the main barrier that inhibits Chinese consumers to purchase in the supermarket is cultural distance. It is found that the supermarket fails to adapt to the local preference and tastes. In addition, the supermarket is considered to be weak in service and distribution sector. These defects result in significant dissatisfaction among Chinese consumers. Due to the difficulties of changing, the author‟s advice is adapting. Consumers‟ attitudes and cultural values are not possible to be changed overnight. The supermarket is expected to obtain a greater market share by adapting to local preference and fully meeting consumers‟ needs.